SiFTL and SiHd3a are positive regulators of flowering time in sesame (Sesamum indicum L.) - Zhao, Fengli; Du, Zhenwei; Cui, Chengqi; Wu, Ke; Jiang, Xiaolin; Wang, Jingjing; Zhang, Ruping; Fan, Yadong; Henry, Robert J.; Liu, Yanyang; Mei, Hongxian; Zhang, Haiyang (Frontiers in Plant Science, 2025)
Flowering time, a critical trait for crop adaptation, is regulated by plants’ ability to sense light signals, which influences gene expression and the transition from vegetative to reproductive growth. In this study, five populations of sesame (Sesamum indicum) were developed by crossing ‘Yuzhi 4’ with ‘BS377’ (late-flowering variety). Linkage mapping analysis revealed that a 400 kb region on chromosome 11 had the most significant and stable effect on flowering time. FLOWERING LOCUS T-like (FTL) and HEADING DATE 3A (Hd3a), located within the candidate region, are associated with flowering time as revealed by RNA-seq and qRT-PCR analyses. Integrated analyses of SiFTL gene structure and transcript level revealed that the absence of SiFTL expression leads to the late-flowering phenotype in BS377. Moreover, SiFTL and SiHd3a, which are highly homologous to Arabidopsis FT and TWIN SISTER OF FT (TSF), are associated with earlier flowering. Furthermore, the Yuzhi 4 haplotypes of SiFTL and SiHd3a locus co-segregated with the early-flowering trait in a recombinant inbred line (RIL) population. In addition, heterologous expression of the Yuzhi 4 haplotypes of SiFTL and SiHd3a significantly accelerated flowering in Arabidopsis Col-0 and the ft-10 mutant under both long-day (LD) and short-day (SD) conditions. These haplotypes may function as universal floral activators downstream of flowering pathways. These findings not only enhance our understanding of the molecular mechanisms controlling flowering time in sesame but also offer valuable genetic resources for breeding early-maturing varieties.